Pengembangan Sistem Informasi Berbasis Web Sebagai Sistem Pengelolaan Nilai Sekolah Menengah Siswa SMP Negeri 2 Satap Kualuh Hilir Dengan Menggunakan Metode End User Computing Satisfacation - Siregar, Ade Elvi Rizki; Harahap, Syaiful Zuhri; Irmayanti, Irmayanti; Bangun, Budianto (Universitas Labuhanbatu, 2025)
Research is a crucial element in the learning process to measure students ' understanding and evaluate the quality of Education. However, the process of managing student grades is often complicated, especially with dynamic curriculum changes in Indonesia, such as the transition from the 2013 curriculum to The Independent curriculum. Based on the problems in SMP Negeri 2 Satap Kualuh Hilir, this study aims to design and build a web-based student Value Management Information System. The development of this system is expected to be a solution to manage value more quickly, accurately, and efficiently. In addition, this system is designed to maximize the utilization of computer network facilities that are already available in schools, so as to assist teachers and schools in producing assessment reports that are in accordance with the applicable curriculum.